The potential of Calliandra calothyrsus as a fodder tree on acidic Nitosols of the southern, western, and southwestern highlands of Ethiopia - Berhe, Kahsay; Mohamed-Saleem, M.A. (Winrock International, 1996)
Four accessions of Calliandra calothyrsus Meissn. (calliandra) and 11 accessions of different Leucaena spp. (leucaena) were evaluated for suitability to improve livestock nutrition in highland small-holder farming systems. Dry matter (DM) yield, response to phosphorus (P) application, and feed quality were measured as indices of adaption on an acidic Nitosol at Soddo, southern Ethiopia. Flowering and seed production were observed. Herbage DM yields of all calliandra accessions were significantly higher than those of the leucaenas, except for L. diversifolia (ILCA 14193). Tree height, spread, stem diameter, and DM yields responded significantly to P application. Calliandra fodder generally has low in vitro dry matter digestibility compared to leucaenas at physiologically similar stages of growth. The clearly superior growth performance of calliandra observed will therefore have to be judged from its usefulness to livestock by in vivo studies at the farm level. While being widely used as a multipurpose tree, calliandra has not been extensively researched for its forage value. There seems to be considerable scope for selecting highly productive and useful lines of calliandra for incorporation into small-holder farming systems in the southern, western, and southwestern highlands of Ethiopia.